Intrinsic electromechanical dynamic equations for piezoelectric power harvesters - Lumentut, M.; Howard, Ian (2017)
This paper discusses, compares and contrasts two important techniques for formulating the electromechanical piezoelectric equations for power harvesting system applications. It presents important additions to existing literature by providing intrinsic formulation techniques of the harvesting system for the two different electromechanical dynamic equation-based voltage and charge-type systems associated with the standard AC–DC circuit interface developed using the extended Hamiltonian principle. The derivations of the two analytical methods rely on the fundamental continuum thermopiezoelectricity concepts of the electrical enthalpy energy and Helmholtz free energy. The benefit of using analytical charge-type modelling is that the technique shows more compact formulation for developing simultaneous derivations by coupling the mechanical and electromechanical systems of the piezoelectric devices and electronic system so that the frequency response functions (FRFs) and time wave form systems can be formulated. On the other hand, the analytical voltage-type modelling is obviously convenient but can show tedious derivation process for joining with the electronic circuit part. To tackle this situation, the analytical voltage type with mechanical and electromechanical forms of the piezoelectric structure can be derived separately from the electronic system where they can be combined together after applying further derivations to formulate the FRFs. In this paper, the two analytical techniques also show particular benefit and even further development of how to model the power harvesting scheme with the combinations of piezoelectric structure and electronic system. Moreover, validations of the two analytical methods show good agreement with previous authors’ electromechanical finite element analysis and experimental works. Further parametric electromechanical energy harvesting behaviours have been explored to study the system responses.